Cuisine of the poor. Vilnius’s intellectual elites in the face of hunger in the first half of the 19th century - Kita, Jarosław; Korybut-Marciniak, Maria; Agnieszka Gralak (Perspektywa stołu, 2023)
The article is an analysis of the problems of malnutrition among the lower social strata in the Lithuanian-Belarusian territories after the partitions. It characterizes the causes of poverty and the development of charitable activities, one of the main goals of which was to eliminate hunger. The source basis are articles by social activists published in Vilnius magazines as well as reports and annual accounts of the Vilnius Charity Society from the first half of the 19th century, which present the diet of pauperized groups covered by philanthropic help.